1985
DOI: 10.1139/v85-497
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton absorption and decomposition studies of chloroform-d induced by a pulsed 13CO2 laser

Abstract: The multiphoton absorption (MPA) and decomposition (MPD) of chloroform-d induced by various "CO, [00°1 4 10°0] lines were studied for pressures from 0.133 to 13.3 kPa. MPA results show a cross-section increasing with pressure up to a plateau value which is likely due to rotational hole-filling. A MPA "spectrum" of the average number of photons absorbed versus wavenumber for different "CO, laser lines is shifted to lower wavenumbers compared to the small signal absorption spectrum by at least 5 cm-' suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…The saturation fluence corresponds to the fluence value for which half the CDCl 3 molecules within the observation region are dissociated. The value of Φ sat obtained is consistent with the values reported by other authors in different experimental conditions [17,18]. The excellent agreement between the In order to prove this hypothesis, we carried out experiments to determine the global dissociation probability per pulse from the measurement of the fraction of molecules dissociated per pulse by infrared spectrometry.…”
Section: Resultssupporting
confidence: 89%
“…The saturation fluence corresponds to the fluence value for which half the CDCl 3 molecules within the observation region are dissociated. The value of Φ sat obtained is consistent with the values reported by other authors in different experimental conditions [17,18]. The excellent agreement between the In order to prove this hypothesis, we carried out experiments to determine the global dissociation probability per pulse from the measurement of the fraction of molecules dissociated per pulse by infrared spectrometry.…”
Section: Resultssupporting
confidence: 89%
“…The PSE method was first applied to CDC13 [ll. At the fluence studied, the dominant term in the expansion was h20 (positive) confirming previous findings [8] that collisional up-pumping processes (sometimes called energy pooling) could be more important than pressure-independent MPD (designated by hlo [5,91). One of the product molecules from CDC13 dissociation, CZC14, absorbed the laser radiation, and a positive hll indicated that it was contributing this energy to the decomposition of the CDC13 molecules through collisional energy transfer.…”
Section: Introductionsupporting
confidence: 86%
“…10.1 1.5 In other experiments in this laboratory, decomposition under similar conditions was second order. 2 Isotope selectivity for CTCl 3 has been observed 9 • 11 • 1O with high separation factors in decomposition of mixtures with CDCl 3 and this appears most compatible with time-dependent first-order ki-.) Also at: National Research Council of Canada, 100 Sussex Drive, Ottawa, Ontario, Canada KIA OR6 b) Dr. Robert A.…”
Section: Introductionmentioning
confidence: 83%